Activation of alcohol yeast - Palianytsia, Liubov; Berezovska, Natalia; Kosiv, Ruslana; Pikh, Zorian; Kharandiuk, Tetiana (Видавництво Львівської політехніки, 2017)
The influence of alcoholic yeast treatment with electrochemically activated water (EAW) on their enzymatic activity in the fermentation and generation, improve their physiological state was investigated. The obtained results showed that catholyte has the greatest effect on alcoholic yeast activity. The use of electrochemically activated water in alcohol production can reduce the duration of the biotechnological process and increase the finished product yield.
Keywords: yeast; enzymatic activity; alcoholic fermentation; electrochemically activated water; catholyte; anolyte